2016
DOI: 10.1111/codi.13288
|View full text |Cite
|
Sign up to set email alerts
|

Survival following salvage abdominoperineal resection for persistent and recurrent squamous cell carcinoma of the anus: do these disease categories affect survival?

Abstract: Persistent and recurrent disease does not show any significant difference in survival, but patients with late recurrence may have a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…In terms of OS, the results of the current series are comparable with previously published data from retrospective series or randomized trials [3][4][5][6][7][8][9][10][11][12][13][14] . In ACC and AMC, surgery should be considered at the time of recurrence as a salvage treatment [15] .…”
Section: Discussionsupporting
confidence: 86%
“…In terms of OS, the results of the current series are comparable with previously published data from retrospective series or randomized trials [3][4][5][6][7][8][9][10][11][12][13][14] . In ACC and AMC, surgery should be considered at the time of recurrence as a salvage treatment [15] .…”
Section: Discussionsupporting
confidence: 86%
“…Twenty‐five studies provided definitions of persistent vs recurrent disease . Twenty‐one studies used 6 months to differentiate persistent from recurrent disease. One study separated recurrent disease into early (between 6 and 24 months) and late (after 24 months).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies used 6 months to differentiate persistent from recurrent disease. One study separated recurrent disease into early (between 6 and 24 months) and late (after 24 months). The remaining four studies did not provide a time period to differentiate persistent from recurrent disease.…”
Section: Resultsmentioning
confidence: 99%
“…van der Wal et al [30] , reported a survival rate of 47% at 5 years in 17 patients with recurrent or persistent disease after surgical salvage treatment. A recent study of Severino et al [31] showed that patients with persistent disease or early recurrence had a significantly higher dis- ease stage than patients with late recurrence. Akbari et al [22] reported that patients with persistent disease had worse prognosis than those with recurrent disease.…”
Section: Oncological Results Of Surgical Salvage Surgerymentioning
confidence: 98%